México: Construcción de identidades - Fernández Poncela, Anna M. (2000)
This text reviews some of the characteristics and the means that have shaped gender identity, as part of the traditional and popular Mexican national identity. It is a matter of reflecting briefly and generally on the subject, with special emphasis, first of all, on the idea that it is a sociocultural construction, and therefore with possibilities for change. And secondly, on how the invented and mythologized image of the national soul is intimately intertwined and linked with the stereotypes and social roles assigned to each sex. This last matter being very peculiar to the Mexican context presented here.